THE CONSUMMATE LOVE OF HAZEL GRACE AS REFLECTED IN THE FAULT IN OUR STARS MOVIE - Astriana, Nadya Novera (LANTERN (Journal on English Language, Culture and Literature), 2017)
The Fault in Our Starsis one of the American romantic movies which shows the struggle to maintain a relationship between a couple who have cancer. This thesis discusses about the consummate love with three aspects of love of Hazel grace and Augustus Waters in The Fault in Our Stars movie. The purpose of this thesis is to analyze the intrinsic aspects and the extrinsic aspects of the movie. The writer uses three methods in analyzing the intrinsic aspects and the extrinsic aspects. Library research is used to collect the data for this thesis. To analyze the intrinsic aspects, the writer uses exponential approach and to analyze the extrinsic aspects, the writer uses psychological approach. In relation to psychological approach, the writer uses Triangular Theory of Love Triangular Theory of Love by Robert Stenberg to explain the extrinsic aspects. Stenberg explains that love has three components which are intimacy, passion, and commitment and consummate love is the combination of those three components of love. The finding of this thesis is the relationship between Hazel Grace and Augustus Waters depicts about consummate love because they brings the complete components of love in the movie.